Psychologia zarządzania emocjami - Błaszczyk, Marek (Człowiek i Społeczeństwo, 2025)
The article presents a critical approach to Emocje. Jak nimi zarządzać [Emotions] by Mike Annesley (Wydawnictwo Bellona, Warszawa 2024). It discusses the main theses presented in the dissertation and invites to reflection on the place and role of emotions in human life.